High-stakes teacher testing in Colorado: the predictive validity of the Professional Knowledge PLACE examination - Mallette, Dawn M., author; Cobb, R. Brian, advisor; Kotsiopulos, Antigone, committee member; Nelson, Barbara J., committee member; Whaley, David C., committee member (Colorado State University. Libraries, 2000)
The purpose of this descriptive survey research was to determine the predictive validity of the Colorado Professional Knowledge PLACE exam, an examination required for teacher licensing. Survey instruments were mailed to 84 novice teachers who completed the teacher licensure program at Colorado State University during the fall 1997 through spring 1999 semesters, fulfilled the requirements for licensing in the state, were employed in secondary schools in Colorado, and could be located. The research questions guiding this study attempted to determine if novice teachers' scores on the Professional Knowledge PLACE examination predicted success in their first or second year of teaching. If a score on this examination is not a predictor, the study sought to determine what additional factors might account for any significant amount of variance in self-rated scores as compared to the scores received on the licensing exam. No significant relationships were found between the self-perceptions of performance and novice teachers' scaled and sub-scores on the Professional Knowledge exam. In addition, when filtered for select levels of several demographic variables, none of them revealed statistically significant relationships between the survey responses and the respondents' examination scores. This research provided results which reveal, to some degree, the lack of any relationship between high-stakes teacher testing and performance in the classroom. The results of this research should be considered by local, state, and national policy makers who formulate policy related to teacher licensing. In addition, the survey instrument used in this study could be utilized by those examining teaching competencies of novice teachers.
Keywords: educational evaluation; teacher education; educational tests and measurements